2019
DOI: 10.1089/heq.2018.0079
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stigma in Health Care Settings and the Physical and Mental Health of People of Color in the United States

Abstract: Purpose: Addressing perceived and enacted stigma in clinical settings is critical to ensuring delivery of high-quality patient-centered care, reducing health disparities, and improving population health outcomes.Methods: Data from the Behavioral Risk Factor Surveillance System's (2012–2014) Reaction to Race module were analyzed to test the hypothesis that perceived stigma in health care settings would be associated with poorer physical and mental health. Poor health was measured by (1) the number of days the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Stigma is the deleterious, structural force that devalues those who hold undesirable characteristics [1]. Stigma is a social process that occurs between groups; this process can occur in-person and online [2][3][4][5][6]. Regardless of setting, research has consistently found that stigma is associated with negative health outcomes [2,4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Stigma is the deleterious, structural force that devalues those who hold undesirable characteristics [1]. Stigma is a social process that occurs between groups; this process can occur in-person and online [2][3][4][5][6]. Regardless of setting, research has consistently found that stigma is associated with negative health outcomes [2,4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…8,11 Studies suggest that stigma is associated with negative health outcomes. [12][13][14] Stigma and discrimination negatively affect public health efforts in diseases such as mental illness, epilepsy, tuberculosis, leprosy, and HIV/AIDS. 8,12,13 Stigma caused people with HIV to hide their disease, avoid voluntary testing and counseling, and not seek for treatment, pushed the epidemic underground.…”
Section: Introductionmentioning
confidence: 99%
“…5,8 Furthermore, stigma may lead people to distrust the government, health professionals, and health care system. 6,12,13 In the context of COVID-19 pandemic, public health measurements taken to contain the outbreak such as mask using, quarantine and isolation fueled stigma towards the disease; 15 therefore, it is imperative that people trust their government and health care systems so that they will be cooperative. 6 Stigma against particular disease is very dangerous, in particular if it comes from HCWs, as it may lead to poor health care service even rejection to treat patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found such discrimination to be one of the factors mediating the relationship between group membership and health outcomes [3][4][5][6][7][8][9]. Given the nature of disparities in health access and outcomes in the United States, where historically African-Americans have shown worse access and outcomes across various indicators, this literature has primarily focused on race/ ethnicity-based discrimination, particularly between whites and African Americans [10][11][12]. In recent years, discrimination research has expanded its scope and found evidence of an association between perceived discrimination and adverse health outcomes among other minority groups also, such as Asian Americans and Hispanic Americans [13,14].…”
Section: Introductionmentioning
confidence: 99%